2010
DOI: 10.1038/jp.2010.22
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum and vaginal fluid C-reactive protein levels do not predict early-onset neonatal infection in preterm premature rupture of membranes

Abstract: Objective: The aim of this study was to evaluate the usefulness of maternal serum and vaginal fluid C-reactive protein (CRP) determinations in the prediction of neonatal congenital infection.Study Design: Fifty women between 24 and 36 weeks gestation, complicated by preterm premature rupture of membranes (pPROM), were divided into two groups according to the presence (n ¼ 14) or absence (n ¼ 36) of early-onset newborns' infection.Result: Maternal serum and vaginal fluid CRP concentrations were comparable betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…A number of studies have assessed the relationship between early-onset neonatal sepsis and the maternal serum CRP level; some studies have demonstrated a significant association (12, 23, 24), while other studies have failed to do so (25, 26). This discrepancy among studies is probably attributable, in part, to a wide variety of time intervals between CRP measurement and delivery.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have assessed the relationship between early-onset neonatal sepsis and the maternal serum CRP level; some studies have demonstrated a significant association (12, 23, 24), while other studies have failed to do so (25, 26). This discrepancy among studies is probably attributable, in part, to a wide variety of time intervals between CRP measurement and delivery.…”
Section: Discussionmentioning
confidence: 99%
“…De trè s nombreuses é tudes ont é valué la valeur pré dictive de la CRP en cas de RPM (Tableau 1) [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: La Prote´ine C-re´active (Crp)unclassified
“…Quatre é tudes ont porté sur la pré diction d'une infection né onatale pré coce chez des femmes ayant une RPM avant terme. Les valeurs pré dictives retrouvé es sont faibles avec, pour des seuils de 10 à 20 mg/l, une sensibilité variant entre 21 % et 56 % et une spé cificité entre 63 % et 95 % et un RV+ entre 1,5 et 4[28,31,33,34].…”
unclassified
“…The development of neonatal infection and its association with maternal CRP levels has been observed previously 11,13,14 . Research carried out at the University of Philadelphia on the variation of maternal serum and vaginal fluid CRP levels identified that both maternal serum and vaginal fluid CRP determinations after prelabor preterm rupture of the membrane are of poor predictive value in neonatal early-onset infection prediction 11 .…”
Section: Discussionmentioning
confidence: 61%
“…However, a study conducted in 1990 suggests serum CRP is a useful and rapidly available adjunct to clinical assessment in the diagnosis and exclusion of bacterial infection in the early neonatal period. This has encouraged us to withhold or discontinue antibiotics and has a role in monitoring Research article response to treatment 13 . Another study carried out in India concludes that being a primi mother, prolonged labour, maternal fever, more than three VEs, rupture of the membrane more than 24 hours, foul smelling liquor, urinary tract infection, and cesarean sections significantly associated with elevated CRP levels after 24 hours of the postpartum period.…”
Section: Discussionmentioning
confidence: 99%